Muslims and India's freedom movement - Shan Muhammad; Institute of Objective Studies (New Delhi, India) (New Delhi : Institute of Objective Studies, 2002)
Covers the period 1857-1947.
Includes bibliographical references (p. [213]-231) and index.
Keywords: Muslims -- Political activity -- India; India -- Politics and government -- 1857-1919.; India -- Politics and government -- 1919-1947.